Hot-dip galvanized aluminum-magnesium coated steel plate with fine surface and preparation method of hot-dip galvanized aluminum-magnesium coated steel plate

By optimizing the chemical composition of zinc-aluminum-magnesium plating and controlling the size of α-Al dendrites, the problem of cracks and surface texture of hot-dip galvanized aluminum-aluminum-coated steel plates during processing is solved, and a plated steel plate with delicate surface and strong corrosion resistance is achieved.

CN119640183APending Publication Date: 2025-03-18SHOUGANG GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411817340.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Hot-dip galvanized aluminum-magnesium-coated steel plates are prone to cracks and surface texture during processing, and their corrosion resistance and processing and forming capabilities are insufficient, which cannot meet the needs of high surface quality.

Method used

By optimizing the chemical composition of zinc-aluminum-magnesium plating, controlling the content of elements such as Mg, Al, Si, Fe, etc., and adding trace elements such as Sr, Zr, Ce, etc. when necessary, optimizing the chemical composition of the plating layer, controlling the primary dendrite arm length of α-Al dendrites is ≤50μm, forming a fine surface plating layer.

Benefits of technology

The surface quality of hot-dip galvanized aluminum-magnesium-coated steel plates is significantly improved, and the coating steel plate products with delicate surfaces, high flatness and strong corrosion resistance are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640183A_ABST
    Figure CN119640183A_ABST
Patent Text Reader

Abstract

The invention relates to a hot-dip galvanized aluminum magnesium coated steel plate with a fine surface and a preparation method thereof, and belongs to the technical field of coating and plating. The coated steel plate comprises a steel substrate and a zinc-aluminum-magnesium coating attached to at least part of the surface of the steel substrate, and the zinc-aluminum-magnesium coating comprises the following chemical components in percentage by mass: 2-7% of Mg, 5-14% of Al, 0.05-1% of Si, 0.05-0.5% of Fe and Zn; the surface of the zinc-aluminum-magnesium coating contains alpha-Al dendritic crystals, and the average length of primary dendritic crystal arms of the alpha-Al dendritic crystals is smaller than or equal to 50 micrometers. By accurately controlling the contents of main elements such as Mg, Al, Si and Fe in the zinc-aluminum-magnesium coating and adding trace elements such as Sr, Zr, Ce, La, B, Ti, Ca and Y when necessary, the chemical composition of the coating can be optimized, so that the primary dendritic arm length of alpha-Al dendritic crystals in the forming process of the coating is obviously reduced, and the finally obtained steel plate has excellent properties such as fine surface, high flatness and high corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and in particular to a hot-dip galvanized aluminum-magnesium coated steel plate with a fine surface and a preparation method thereof. Background Art

[0002] In recent years, in order to improve the corrosion resistance of steel structures in the construction field, a wave of using hot-dip coated steel plates has emerged. Commonly used hot-dip coated steel plates include hot-dip galvanized steel plates, hot-dip aluminum-zinc coated steel plates, etc. Among them, galvanized steel plates are hot-dip galvanized steel plates, and a layer of pure zinc with a thickness of 50 to 120 microns is covered on the surface of the steel plate. Since the pure zinc layer corrodes slowly in the atmosphere, its corrosion resistance is better than that of steel plates. In order to further improve the corrosion resistance of galvanized plates and save the use of zinc, aluminum is added to zinc. For example, hot-dip aluminum-zinc coated steel plates are developed. Hot-dip aluminum-zinc coated steel plates are also manufactured using hot-dip plating technology. During the solidification process of the molten aluminum-zinc coating, a dendritic aluminum-rich phase will first be formed. Between these dendritic aluminum-rich phases, a zinc-rich eutectic structure that solidifies last will be formed. Since the growth morphology of the aluminum-rich phase is complex and dendritic, it is difficult for corrosion to spread, thereby reducing the corrosion rate and improving the corrosion resistance of the coating.

[0003] However, this aluminum-zinc coating contains a large number of coarse aluminum-rich dendrites, which makes the coating processability poor. After processing, the coating is prone to visible cracks. At the same time, the surface of the coating also presents visible textures, which is not conducive to surface beautification in many occasions. In order to improve the processing and forming ability of the coating while maintaining corrosion resistance, the aluminum in the coating can be reduced, and an appropriate amount of magnesium can be added to achieve the effect of improving corrosion resistance and processing and forming ability. However, this zinc-aluminum-magnesium coated steel plate containing aluminum and magnesium will have an uneven surface under certain conditions, poor fineness, and a touch feeling, which cannot meet the high surface quality requirements. Summary of the invention

[0004] The present application provides a hot-dip galvanized aluminum-magnesium coated steel plate with a fine surface to solve the following technical problem: how to improve the surface quality of the hot-dip galvanized aluminum-magnesium coated steel plate.

[0005] In the first aspect, the present application provides a hot-dip galvanized aluminum-magnesium coated steel plate with a fine surface, the coated steel plate comprising a steel substrate and a zinc-aluminum-magnesium coating attached to at least a portion of the surface of the steel substrate, and the chemical composition of the zinc-aluminum-magnesium coating comprises, by mass fraction: Mg: 2% to 7%, Al: 5% to 14%, Si: 0.05% to 1%, Fe: 0.05% to 0.5%, Zn;

[0006] The surface of the zinc-aluminum-magnesium coating contains α-Al dendrites, and the average length of a primary dendrite arm of the α-Al dendrite is ≤50 μm.

[0007] Optionally, the chemical composition of the zinc-aluminum-magnesium coating includes: Mg: 2%~7%, Al: 5%~14%, Si: 0.05%~1%, Fe: 0.05%~0.5%, Sr: 0.001%~0.01%, Zr: 0.001%~0.01%, Ce: 0.0002%~0.01%, La: 0.0002%~0.01%, B: 0.002%~0.1%, Ti: 0.002%~0.01%, Ca: 0.002%~0.02%, Y: 0.002%~0.02%, Zn.

[0008] Optionally, an alloy layer is contained between the zinc-aluminum-magnesium coating and the steel substrate.

[0009] Optionally, the alloy layer is composed of Al-Fe system compounds.

[0010] Optionally, the average thickness of the alloy layer is 0.03 μm to 1 μm.

[0011] Optionally, the surface micro-undulation height of the zinc-aluminum-magnesium coating does not exceed 10 μm.

[0012] In a second aspect, the present application provides a method for preparing the hot-dip galvanized aluminum-magnesium coated steel sheet described in the first aspect, the method comprising:

[0013] The steel substrate is subjected to annealing treatment;

[0014] The steel substrate after annealing is subjected to continuous hot-dip treatment to obtain a hot-dip zinc-aluminum-magnesium coated steel plate with a fine surface.

[0015] Optionally, the end point temperature of the annealing treatment is 400°C to 450°C.

[0016] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0017] The present application provides a hot-dip galvanized aluminum-magnesium coated steel sheet with a fine surface, the coated steel sheet comprises a steel substrate and a zinc-aluminum-magnesium coating attached to at least part of the surface of the steel substrate, the chemical composition of the zinc-aluminum-magnesium coating comprises, by mass fraction: Mg: 2% to 7%, Al: 5% to 14%, Si: 0.05% to 1%, Fe: 0.05% to 0.5%, Zn; the surface of the zinc-aluminum-magnesium coating contains α-Al dendrites, and the average length of the primary dendrite arm of the α-Al dendrite is ≤50μm. By precisely controlling the content of the main elements such as Mg, Al, Si, and Fe in the zinc-aluminum-magnesium coating, and adding trace elements such as Sr, Zr, Ce, La, B, Ti, Ca, and Y when necessary, the chemical composition of the coating can be optimized, so that the length of the primary dendrite arm of the α-Al dendrite is significantly reduced during the formation of the coating, so that the final steel sheet has excellent properties such as fine surface, high flatness, and strong corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0020] Figure 1 A schematic flow chart of a method for preparing a hot-dip galvanized aluminum-magnesium coated steel plate with a fine surface provided in an embodiment of the present application. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0022] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0023] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the weight ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the weight of substance A: the weight of substance B: the weight of substance C = 1:2:3.

[0024] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.

[0025] In the first aspect, the present application provides a hot-dip galvanized aluminum-magnesium coated steel plate with a fine surface, the coated steel plate comprising a steel substrate and a zinc-aluminum-magnesium coating attached to at least a portion of the surface of the steel substrate, and the chemical composition of the zinc-aluminum-magnesium coating comprises, by mass fraction: Mg: 2% to 7%, Al: 5% to 14%, Si: 0.05% to 1%, Fe: 0.05% to 0.5%, Zn;

[0026] The surface of the zinc-aluminum-magnesium coating contains α-Al dendrites, and the average length of a primary dendrite arm of the α-Al dendrite is ≤50 μm.

[0027] α-Al dendrite is a microstructure formed during the solidification of aluminum (Al)-based alloys. In many aluminum alloys, the α-Al phase usually exists as a matrix phase, and its growth in the form of dendrites is a common solidification structure morphology. The primary dendrite arm is the basic component of the dendrite structure. The word dendrite (dendrite) comes from the ancient Greek word (dendron), which means tree. The primary dendrites, secondary dendrites, tertiary dendrites and higher dendrites in its structure are like branches on a tree. The primary dendrite arm spacing (λ1) is one of the important characteristic dimensions that characterize dendrites. These dendrite arms gradually grow and interact with each other during the solidification of the alloy, which has an important influence on the properties of the final solidified structure.

[0028] The present application provides a hot-dip galvanized aluminum-magnesium coated steel plate with a fine surface. By optimizing the coating composition, controlling the production process and adopting comprehensive measures such as subsequent treatment, the surface quality of the hot-dip galvanized aluminum-magnesium coated steel plate can be significantly improved, and a coated steel plate product with a fine, uniform, dense surface and excellent corrosion resistance can be obtained.

[0029] In some embodiments, the chemical composition of the zinc-aluminum-magnesium coating includes: Mg: 2% to 7%, Al: 5% to 14%, Si: 0.05% to 1%, Fe: 0.05% to 0.5%, Sr: 0.001% to 0.01%, Zr: 0.001% to 0.01%, Ce: 0.0002% to 0.01%, La: 0.0002% to 0.01%, B: 0.002% to 0.1%, Ti: 0.002% to 0.01%, Ca: 0.002% to 0.02%, Y: 0.002% to 0.02%, Zn.

[0030] There is no particular limitation on the steel substrate, and common steel plates such as hot-rolled steel plates and cold-rolled steel plates can be used. There is no particular limitation on the type of steel, and for example, aluminum-killed steel, ultra-low carbon steel, and high-strength steel can be used.

[0031] The positive effect of limiting the Mg content to 2% to 7% is that the Mg in the coating can significantly improve the atmospheric corrosion resistance of the coating. The mechanism is that the Mg in the coating will preferentially dissolve into the water film on the surface of the coating in the atmospheric environment, react with the dissolved carbon dioxide in the water film, and precipitate a dense protective film. This protective film can stably exist in a neutral and weakly alkaline environment, and can also cause the electrolyte solution on the surface of the coating to become a weakly alkaline solution, thereby improving the corrosion resistance of the coating. The Mg in the coating preferentially combines with Zn to form a Mg-Zn compound, and then combines with Si to form a Mg-Si compound. If the Mg content is higher than 7%, large pieces of Mg-Zn compounds are likely to appear during hot dip plating. Large pieces of Mg-Zn compounds often appear together with η-Zn to form a binary eutectic structure. The increase in the binary eutectic structure leads to a decrease in corrosion resistance. Therefore, the Mg content in the coating is limited to 2% to 7%. As a preferred solution, the Mg content in the coating is in the range of 3% to 5%. For example, the content of Mg may be 2%, 3%, 4%, 5%, 6%, 7%, etc.

[0032] The positive effect of limiting the Al content to 5% to 14% is that the Al in the coating provides the coating with high-quality atmospheric corrosion resistance, because during the corrosion process, Al can form dense oxides and dense hydroxides on the surface. If the Al content in the coating is less than 5%, the bonding between the coating and the steel plate will be very poor, resulting in the coating being unusable and reducing corrosion resistance. However, if the Al content in the coating is higher than 14%, a lot of coarse α-Al phases will be formed when the coating is formed. The coarse α-Al phase will form a microscopic uneven texture on the surface of the coating, affecting the aesthetic effect of the coating surface. In addition, Al helps to form Al-Fe system compounds between the coating and the steel matrix. Therefore, the Al content in the coating is limited to 5% to 14%. As a preferred embodiment, the Al content in the coating is in the range of 7% to 12%. Exemplarily, the Al content can be 5%, 7%, 9%, 11%, 13%, 14%, etc.

[0033] The positive effect of limiting the Si content to 0.05% to 1% is that Si can form compounds with Mg to avoid the appearance of large Mg-Zn compounds and large binary eutectic structures, while a Si content higher than 1% will cause the precipitation of elemental Si particles in the coating, deteriorating the corrosion resistance of the coating, and also causing the Fe-Al alloy layer to be destroyed by Mg-Si compounds, resulting in the alloy layer being too thin. For example, the Si content can be 0.05%, 0.1%, 0.3%, 0.5%, 1%, etc.

[0034] The positive effect of limiting the Fe content to 0.05% to 0.5% is that the Fe in the coating mainly interacts with the α-Al dendrites. When the coating solidifies, Fe and Al can form Fe-Al compound particles with a higher melting point. Such Fe-Al compound particles can act as nucleation points of the α-Al phase during the solidification of the coating, thereby increasing the nucleation rate of the α-Al phase, promoting the refinement of α-Al, and significantly reducing the length of the primary dendrite arm of the α-Al dendrite. This is conducive to improving the forming performance of the coating and improving the surface quality. At the same time, the addition of Fe is conducive to the formation of a dense Fe-Al alloy layer between the coating and the steel plate. However, a Fe content higher than 0.5% will result in the appearance of larger-sized Al-Fe compounds in the coating, resulting in reduced corrosion resistance of the coating, and it is also easy to form an overly thick Fe-Al alloy layer. Exemplarily, the Fe content can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.

[0035] The positive effect of limiting the Sr content to 0.001% to 0.01% is that Sr can form fine intermetallic compounds with Al in the coating, serving as the nucleation core of α-Al, thereby increasing the nucleation rate of the α-Al phase, promoting the refinement of α-Al, and significantly reducing the length of the primary dendrite arm of the α-Al dendrite. At the same time, Sr can cause the MgZn2 phase in the binary eutectic structure to break, thereby avoiding the appearance of large pieces of binary eutectic structure. Exemplarily, the Sr content can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, etc.

[0036] The positive effect of limiting the Zr content to 0.001% to 0.01% is that Zr can refine the grain structure of the coating, enhance the density and stability of the coating, and thus extend the service life of the coating. For example, the Zr content can be 0.001%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, etc.

[0037] The positive effect of limiting the Ce content to 0.0002% to 0.01% is that the addition of Ce helps to form Ce oxides on the surface of the coating, thereby improving the corrosion resistance of the coating. For example, the Ce content can be 0.0002%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, etc.

[0038] The positive effect of limiting the La content to 0.0002% to 0.01% is that La, as one of the rare earth elements, has unique chemical properties and can enhance the corrosion resistance of the coating. Adding La in an appropriate amount can refine the coating structure and reduce the penetration path of the corrosive medium, thereby improving the coating's resistance to various corrosive environments. For example, the La content can be 0.0002%, 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, etc.

[0039] The positive effect of limiting the B content to 0.002% to 0.1% is that B mainly interacts with α-Al dendrites in the coating. B can react with Al to form Al-B compound particles, which are first precipitated during the hot-dip plating process to provide a nucleation core for α-Al, thereby refining the α-Al dendrites and significantly reducing the length of the primary dendrite arm of the α-Al dendrite. This is beneficial to improving the forming properties of the coating and improving the surface quality. Exemplarily, the B content can be 0.002%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, etc.

[0040] The positive effect of limiting the Ti content to 0.002% to 0.01% is that Ti can also form fine intermetallic compounds with Al, serving as the nucleation core of α-Al, thereby increasing the nucleation rate of the α-Al phase, promoting the refinement of α-Al, and significantly reducing the length of the primary dendrite arm of the α-Al dendrite. For example, the Ti content can be 0.002%, 0.004%, 0.006%, 0.008%, 0.01%, etc.

[0041] The positive effect of limiting the Ca content to 0.002% to 0.02% is that the addition of Ca can form stable compounds or microstructures with Zn in the coating, which can slow down the degradation rate of the coating in a corrosive environment, thereby improving the overall corrosion resistance of the coating. For example, the Ca content can be 0.002%, 0.005%, 0.008%, 0.011%, 0.014%, 0.017%, 0.02%, etc.

[0042] The positive effect of limiting the Y content to 0.002% to 0.02% is that Y is a rare earth element with excellent chemical stability. Adding an appropriate amount of Y to the coating can enhance the corrosion resistance of the coating, so that the steel plate has a longer service life in harsh environments (such as moisture, acid and alkali, etc.). Y may enhance corrosion resistance by refining grains, forming stable compounds, or increasing the density of the coating. Exemplarily, the Y content can be 0.002%, 0.005%, 0.008%, 0.011%, 0.014%, 0.017%, 0.02%, etc.

[0043] The specific content / content range of Zn can be obtained by the upper and lower limit formula of the component, namely:

[0044] The sum of the percentages of the contents of each component in a composition should be equal to 100%, and the content ranges of several components should meet the following conditions: the upper limit value of a component + the lower limit value of other components ≤ 100; the lower limit value of a component + the upper limit value of other components ≥ 100.

[0045] The positive effect of limiting the average length of the primary dendrite arms of the surface α-Al dendrites of the zinc-aluminum-magnesium coating to ≤50μm: the coarse α-Al phase has poor processing performance and is prone to breakage during forming, resulting in a decrease in the corrosion resistance of the coating. Therefore, the average length of the primary dendrite arms of the α-Al dendrites is required to be ≤50 microns. Exemplarily, the average length of the primary dendrite arms of the surface α-Al dendrites of the zinc-aluminum-magnesium coating can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, etc.

[0046] In some embodiments, an alloy layer is contained between the zinc-aluminum-magnesium coating and the steel substrate.

[0047] In some embodiments, the alloy layer is composed of an Al-Fe system compound.

[0048] Al-Fe system compounds include Al5Fe2 phase with an atomic ratio of 5:2, and its unit cell parameters are α=β=γ=90°, the space group is Cmcm, and it also includes the Al3Fe phase with an atomic ratio of 3:1, and its unit cell parameters are α=γ=90°, β=107.72°, and the space group is C2 / m. The embodiment of the present application can effectively improve the processing performance of the coating and avoid cracking of the coating by forming an alloy layer of Fe-Al compounds between the coating and the steel substrate. The formation of Fe-Al compounds is beneficial to the refinement of the α-Al phase in the coating. This is because the formation of the Fe-Al compound layer can effectively reduce the local Al concentration in the coating, thereby reducing the growth rate of the α-Al phase and reducing its size.

[0049] In some embodiments, the alloy layer has an average thickness of 0.03 μm to 1 μm.

[0050] The average thickness of the alloy layer is greater than 1 μm, which will lead to a decrease in the corrosion resistance of the coating. In addition, the concentration of Al in the local area of ​​the coating will be too low, which will significantly reduce the nucleation rate of the α-Al phase and lead to a larger α-Al phase. For example, the average thickness of the alloy layer can be 0.03 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1 μm, etc.

[0051] In some embodiments, the surface micro-undulation height of the zinc-aluminum-magnesium coating does not exceed 10 μm.

[0052] Figure 1 A schematic flow chart of a method for preparing a hot-dip galvanized aluminum-magnesium coated steel plate with a fine surface provided in an embodiment of the present application.

[0053] See also Figure 1 In a second aspect, the present application provides a method for preparing the hot-dip galvanized aluminum-magnesium coated steel sheet described in the first aspect, the method comprising:

[0054] S1, annealing the steel substrate;

[0055] S2. The steel substrate after annealing is subjected to continuous hot-dip treatment to obtain a hot-dip zinc-aluminum-magnesium coated steel plate with a fine surface.

[0056] In some embodiments, the end point temperature of the annealing treatment is 400°C to 450°C.

[0057] The positive effect of limiting the end temperature of the annealing treatment to 400℃~450℃: Before the continuous hot-dip treatment, the steel substrate is usually annealed. After annealing, cool to an appropriate temperature and then perform hot-dip treatment. If the end temperature after annealing is higher than 450℃, the coating will solidify very slowly on the surface of the steel substrate, allowing the α-Al phase in the coating to grow fully, which may form a larger α-Al phase. If the end temperature after annealing is lower than 400℃, it will make it difficult for the Fe-Al compound layer to form between the coating and the steel plate, and it will also cause the size of the α-Al phase to increase. Exemplarily, the end temperature of the annealing treatment can be 400℃~450℃, etc.

[0058] The present application is further described below in conjunction with specific embodiments. The experimental methods in the following embodiments that do not specify specific conditions are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0059] In Examples 1-5 and Comparative Examples 1-5, a steel substrate with a thickness of 4.5 mm and a width of 1000 mm was used, and the weight of the zinc-aluminum-magnesium coating was 150 g / m2 on a single side. In Examples 6-10 and Comparative Examples 6-10, a steel substrate with a thickness of 1.5 mm and a width of 1500 mm was used, and the coating weight was 150 g / m2 on a single side. The composition of the zinc-aluminum-magnesium coating and the average thickness of the Al-Fe system compound alloy layer are shown in Table 1, and the end point temperature of the annealing treatment is shown in Table 2.

[0060] The average thickness of the alloy layer between the coating and the steel substrate can be measured by the following method:

[0061] A sample of 10 mm×10 mm in size is prepared from the coated steel sheet involved in this embodiment, and a thin sample containing an alloy layer is cut from the coating layer using a focused ion beam process. The thickness of the thin sample should be suitable for transmission electron microscopy observation. The thin sample is then observed under a transmission electron microscope to measure the thickness of the alloy layer.

[0062] Table 1 Composition of zinc-aluminum-magnesium coating (wt%), average thickness of Al-Fe system compound alloy layer (μm)

[0063]

[0064] Table 2 analyzes the characteristics of the microstructure of the coating surface of the embodiment and the comparative example.

[0065] The length of the primary dendrite arm of the α-Al dendrite on the surface of the coating can be measured by the following method:

[0066] A sample of 10 mm × 10 mm in size was prepared from the coated steel plate involved in the present embodiment. The sample was surface polished using electrolytic polishing technology. The surface of the coating was then analyzed using a scanning electron microscope and its accompanying energy spectrum analysis equipment. The α-Al phase was determined based on the enrichment distribution position of Al. The length of the primary dendrite arm of each α-Al phase was calculated using image analysis software. Five fields of view were collected for each sample, and a total of five samples were analyzed. The arithmetic mean of the length of the primary dendrite arm of the α-Al phase in all fields of view of the five samples was calculated.

[0067] The corrosion resistance of the coating was evaluated using the JASO (M609-91) cyclic corrosion test. The cyclic corrosion test was performed for 100 cycles. If the corrosion weight loss of the coating reached 80g / m 2 , the corrosion resistance is evaluated as C. If the corrosion weight loss of the coating is 60-80g / m 2 If the corrosion loss of the coating is between 50-60g / m 2 If the corrosion weight loss of the coating does not exceed 50g / m 2 , the corrosion resistance is evaluated as AA.

[0068] White light interferometer is used to analyze the height of the unevenness on the coating surface. The Sa parameter is used to evaluate the unevenness height of the coating surface. If Sa exceeds 15 microns, the surface quality is evaluated as C. If Sa is 10-15 microns, the surface quality is evaluated as B. If Sa is less than 10 microns, the surface quality is evaluated as A.

[0069] The corrosion resistance and surface quality evaluation results of the coating are shown in Table 2.

[0070] Table 2 End point temperature of annealing treatment, microstructure characteristics of coating surface, corrosion resistance and surface quality evaluation results of coating

[0071] Group Annealing end point temperature / ℃ Length of primary dendrite arm of α-Al dendrite / μm Surface quality evaluation level Corrosion resistance grade Example 1 450 10 A AA Example 2 440 25 A AA Example 3 440 20 A AA Example 4 410 50 A A Example 5 410 40 A A Comparative Example 1 490 110 C B Comparative Example 2 470 80 C B Comparative Example 3 390 60 B C Comparative Example 4 385 70 C C Comparative Example 5 460 75 B C Example 6 400 35 A AA Example 7 400 30 A AA Example 8 420 25 A AA Example 9 420 20 A A Example 10 410 50 A A Comparative Example 6 390 60 B C Comparative Example 7 390 55 B C Comparative Example 8 460 100 C B Comparative Example 9 470 120 C B Comparative Example 10 470 60 B B

[0072] It can be seen from Table 1-2 that in Examples 1 to 10, the composition of the coating and the microstructure characteristics of the coating surface are both within the required range of the present invention, with good corrosion resistance and surface quality.

[0073] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0074] The hot-dip galvanized aluminum-magnesium coated steel sheet provided by the embodiment of the present invention has good corrosion resistance and a fine surface. In the microstructure of the coating surface, the average length of the primary dendrite arm of the α-Al dendrite is ≤50 μm.

[0075] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A hot-dip galvanized aluminum-magnesium coated steel sheet with a fine surface, the coated steel sheet comprising a steel substrate and a zinc-aluminum-magnesium coating attached to at least a portion of the surface of the steel substrate, wherein the chemical composition of the zinc-aluminum-magnesium coating comprises, by mass fraction: Mg: 2%~7%, Al: 5%~14%, Si: 0.05%~1%, Fe: 0.05%~0.5%, Zn; The surface of the zinc-aluminum-magnesium coating contains α-Al dendrites, and the average length of a primary dendrite arm of the α-Al dendrite is ≤50 μm.

2. The hot-dip galvanized aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The chemical composition of the zinc-aluminum-magnesium coating includes: Mg: 2%-7%, Al: 5%-14%, Si: 0.05%-1%, Fe: 0.05%-0.5%, Sr: 0.001%-0.01%, Zr: 0.001%-0.01%, Ce: 0.0002%-0.01%, La: 0.0002%-0.01%, B: 0.002%-0.1%, Ti: 0.002%-0.01%, Ca: 0.002%-0.02%, Y: 0.002%-0.02%, Zn.

3. The hot-dip galvanized aluminum-magnesium coated steel sheet according to claim 1, characterized in that: An alloy layer is contained between the zinc-aluminum-magnesium coating and the steel substrate.

4. The hot-dip galvanized aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The alloy layer is composed of an Al-Fe system compound.

5. The hot-dip galvanized aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The average thickness of the alloy layer is 0.03 μm to 1 μm.

6. The hot-dip galvanized aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The surface microscopic undulation height of the zinc-aluminum-magnesium coating does not exceed 10 μm.

7. A method for preparing a hot-dip galvanized aluminum-magnesium coated steel sheet according to claims 1 to 6, characterized in that: The method comprises: The steel substrate is subjected to annealing treatment; The steel substrate after annealing is subjected to continuous hot-dip treatment to obtain a hot-dip galvanized aluminum-magnesium coated steel sheet.

8. The method according to claim 7, characterized in that The end point temperature of the annealing treatment is 400°C to 450°C.